2013
DOI: 10.1007/s00405-013-2642-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative results of infratemporal fossa approach with or without facial nerve rerouting in jugular fossa tumors

Abstract: Jugular fossa tumors are uncommon diseases. During the surgery and due to the interposition of the facial nerve in the tumor approach, the facial nerve must be elevated from the fallopian canal and placed permanently into an anterior position. Although this maneuver provides a wide exposure, most of the patients suffer a long-term total or partial facial palsy. The purpose of this article is to check whether the infratemporal fossa approach without transposition of the facial nerve is equivalent to the approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…11 They consider this approach to have limited indications because it is very difficult to remove extensive jugular paragangliomas while leaving the facial nerve in situ. 12 In the non-rerouting group, total tumour resection was achieved in 64 per cent of patients, and House-Brackmann grade I-II function in 100 per cent. However, Russo and colleagues consider this approach to be indicated for non-vascular jugular foramen tumours that do not infiltrate the surrounding bone or ICA adventitia, such as lower cranial nerve schwannomas and meningiomas.…”
Section: Non-rerouting Techniquementioning
confidence: 93%
“…11 They consider this approach to have limited indications because it is very difficult to remove extensive jugular paragangliomas while leaving the facial nerve in situ. 12 In the non-rerouting group, total tumour resection was achieved in 64 per cent of patients, and House-Brackmann grade I-II function in 100 per cent. However, Russo and colleagues consider this approach to be indicated for non-vascular jugular foramen tumours that do not infiltrate the surrounding bone or ICA adventitia, such as lower cranial nerve schwannomas and meningiomas.…”
Section: Non-rerouting Techniquementioning
confidence: 93%
“…Hence, it is desirable to either work around it or, if not possible, rerouting is needed before tumor is removed. 6 Llorente et al 7 found no difference in the surgical exposure attained or the tumor removal possible by mobilizing (rerouting) the temporal part of the facial nerve. Contradicting this are studies of cadaveric dissection by Von Doersten and Jackler, 8 which quote a wider corridor for surgery and lesion removal as well as fewer recurrences 9 on rerouting the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The hypervascular nature of these tumors further complicates surgical management. Despite advances in surgery [17,18], extensive resection of GJT has great potential to leave the patients with substantial treatment-related morbidity, which should be considered as a high cost for the management of a mostly benign tumor [19][20][21].…”
Section: Practice Pointsmentioning
confidence: 99%